O projeto In Tlilli in Tlapalli - Imágenes de la nueva tierra como estratégia de descolonização epistêmica - Marziale, Nicole Palucci (Revista do Colóquio, 2020)
This paper starts from the study of the project In Tlilli in Tlapalli - Imágenes de la nueva tierra: identidad indígena después de la conquista, developed by researcher Diana Magaloni Kerpel and visual artist Mariana Castillo Deball, which resulted in the organization of an exhibition at the Amparo Museum, in Puebla, México. The exhibition had the purpose of presenting the indigenous perspective of the Spanish conquest of México, in the Mesoamerican context, as well as the subjectivities and cosmovision of these peoples, by working with historical copies and facsimiles of the colonial codices, as well as “maps-paintings”. We intend to approach the exhibition’s proposals, along with some of the documents that were displayed, relating them with epistemic decolonization propositions, which defend the need of evidencing, contemporarily, the knowledges supplanted by western knowledge and the modern/colonial reason.